Combinatorial synthesis of optimal plans of multifactor experiment - Костенко, О. М. (Scientific Progress & Innovations, 2016)
The problem of constructing an optimal plan may be solved by a software and reference-catalog of typical solutions. For this it is advisable to develop a system of automation of scientific and technical experiments that will enable the cut-timing of the experimental studies and reduce costs for them, release experimenter from routine operations and perform complex experiments. A compositive method of construction plans of multifactor experiment close to optimal for a number of factors (10 or more), based on multi-track local-optimal plans of MFE. We considered decisions of by-stage tasks method, there are examples of building of MFE plans using the best local MFE plans. Overapplication of the offered method will help to simplify the process of building of close to the optimum MFE plans for a large number of factors.